LEFT-VENTRICULAR MASS ESTIMATED BY M-MODE ECHOCARDIOGRAM IS NOT ALTERED BY CHANGES IN CARDIAC SHAPE AND DIMENSIONS DUE TO ACUTE ARTERIAL-HYPERTENSION - Matsubara, Beatriz Bojikian [UNESP]; Bregagnollo, E. A.; Tucci, PJF (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
The effect of changes in left ventricular (LV) shape and dimensions due to acute arterial hypertension induced by mechanical obstruction of the aorta for 10 min on LV mass values estimated by M-mode echocardiogram was studied in 14 anesthetized dogs. Although the systolic pressure increased from 117.5 +/- 19.9 to 175.4 +/- 22.9 mmHg altered ventricular diameter from 2.77 +/- 0.49 cm to 3.17 +/- 0.67 cm (P<0.05) and wall thickness from 0.83 +/- 0.09 to 0.75 +/- 0.09 cm (P<0.05), LV mass estimated before (73.5 +/- 19.1 g) and after (78.3 +/- 26.4 g) hypertension was not significantly different. We demonstrate here for the first time that changes in LV dimensions induced by acute arterial hypertension do not modify LV mass values estimated by the M-mode electrocardiogram method.
Keywords: VENTRICULAR MASS; ACUTE ARTERIAL HYPERTENSION; M-MODE ECHOCARDIOGRAM